The role of alternative assessment on the writing domain of the english composition courses enrolled in the english teaching bachelor degree at the Foreign Language Department of the University of El Salvador. Licenciatura thesis, Universidad de El Salvador. - Cárcamo Díaz, Roxana Ercilia
This study aimed to identify the role of alternative assessment on the writing domain of English Composition courses enrolled in English Teaching Bachelor Degree at the Foreign Language Department of the University of El Salvador. Accordingly, observation forms, a semi-structured interview (five teachers) and a performance checklist (28 students) were created. It was determined that traditional assessment is the approach most used by English Composition teachers even when they implemented some alternative assessment strategies as well. Besides, writing samples, teacher-student conference, and conference with the whole class, learning log, journal, chart book, teacher feedback and peer-assessment were the alternative assessment strategies implemented by English composition teachers. The alternative assessment strategy most by English composition teachers were conference with the whole class and peer assessment. Therefore, the results suggested the need for further research to investigate other alternative assessment strategies to assess writing domain in future English Composition courses from students' perspective.